The impact of TikTok videos in creative designs of house plans in civil technology’s practical assessment tasks - Thokozani Isaac Mtshali (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
The internet bandwidth has drastically improved since most schools have introduced multimodal teaching and learning. This allowed many students to explore various online learning platforms in search of expanded knowledge and skills. Like many other teenage students, Civil Technology students ventured into TikTok videos to learn and share ideas about designing house plans which they used to do a compulsory practical assessment task (PAT). This study explored students' experiences on how TikTok videos have opened doors for creativity in designing house plans, granny flats in particular. A qualitative research method was used, and a case study design was used for sixteen (16) civil technology students who were purposefully sampled to become respondents to the questions posed. Focused group interviews and document analysis were used to gather data and thematic as well as content analysis were used to analyse the sets of data. This study found that the students acquired more creative ways on TikTok to design single-storey house plans. They learned that they could design domestic houses without bricks or timber walls, but also glasses or shipping containers through 3D design. This increased their spatial ability to understand how house plans could be designed using various materials. Thus, this study recommends for habitual use of TikTok videos and live sessions to learn civil technology-building concepts to advance creativity when doing practical assessment tasks.